AKTUALISASI KETENTUAN PIDANA BERDASARKAN UNDANGUNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP (Studi Kasus PT Gamatara Trans Ocean Shipyard, Pelaku Pidana Lingkungan di Cirebon Divonis Denda Rp 2 Miliar) - Efan Setiadi (JURNAL TECHLINK, 2020)
The problem of environmental crime is one of the problems that is rarely heard, both in television news and in public discussions. Three times environmental laws were issued in 1982, 1997 and 2009. The author is interested in examining the application of these provisions to Environmental Criminals in Cirebon, namely PT Gamatara Trans Ocean Shipyard, who was sentenced to a fine of 2 billion and from the news reference of the author of the study. It turns out that this is the first environmental criminal case to be brought to trial in the Cirebon area. For the author, the actualization or application of these provisions is a step or history that can have an impact on people who ignore the environment. The author conveys several things in this paper, both the meanings and also the newsrelated to the titles above. In this study the authors used the literature study method, which was obtained from a number of literature including books that could support the content, sites through the internet network related to the title and discussion. At the end, the author takes part of the criminal provisions contained in UUPPLH 2009 which can be applied to PT. Gamatara.